Process of settlement of Western Ukraine before the 14th centure (space-time aspect) - Krul, Volodymyr; Krul, Halyna (Kosice, Slovakia, 2016)
2039 settlements that emerged during the Early Paleolithic – Old Rus’ time were discovered in Western Ukraine territory and registered in a geoinformation data bank. Phasing (identification of time spans) of settlements emergence based on the universal duration of archeological cultures is carried out, twelve stages identified. The time of the first settlements emergence in the territories of administrative districts is analyzed. The 2nd and the 3rd millennia BCE (stages IX and VIII) were the period of active settlement formation when the settlements emerged in the territories of 107 and 105 Western Ukraine administrative districts (about 95 and 93% of their total number in the region), respectively.
Keywords: settlement processes; prehistoric settlements; arcgeological antiquities; the intensity of the settlement; settlement development